Trucking (un)limited: The impact of digital platforms on labour in production networks of logistics - Veronique Helwing; Philip Verfürth; Martin Franz (ZFW - Advances in Economic Geography, 2023)
For many years, struggles over value capture have been taking place between different actors in the logistics sector, creating ever more pressure for workers in traditional activities of logistics. New actors, in the form of digital business-to-business (B2B) platforms, which are proliferating especially in the freight transport sector, are further challenging the already contested field. Based on the Global Production Networks (GPN) approach, this study addresses the question of how B2B platforms affect labour in production networks of logistics, and what labour agency practices are emerging in the face of advancing platformisation. The study draws on interviews with various actors operating in the road freight transport sector in Germany. The results show that digital B2B platforms, due to their intermediary function, have a direct impact on the inclusion and exclusion of actors involved in production networks of logistics, and induce not only a race to the bottom in terms of labour conditions, but also produce increasingly contingent geographies of logistics. This paper contributes to the literature on platforms by examining previously neglected B2B platforms and shedding light on the different ways that labour in global production networks can be affected by new agents, such as digital platforms.
Keywords: 330; digitalisation; freight transport; Germany; Global Production Networks; intermediaries; labour agency; platformisation; subcontracting